Postpartum hemorrhage its association with inadequate prenatal care and contribution to burden of disease - Tan, Alvin G.
Due to the advancements in obstetrics, the use of mortality data became a less sensitive measure of the success of obstetric interventions. A more appropriate indicator, as advocated by the WHO, is a measure that combines mortality and morbidity information to estimate population health. On the other hand, even though it has been practiced for a long time, very few systematic evaluations have been done to assess the effectiveness of prenatal care services in preventing the occurrence of maternal morbidity, such as postpartum hemorrhage. These are the main reasons for the conduct of the present study. In particular, this study has two objectives: (1) to determine the association between adequate prenatal care and the occurrence of postpartum hemorrhage; and (2) to estimate the burden of disease attributable to postpartum hemorrhage. For the 1st objective, a secondary analysis of 2000 Family Planning and Reproductive Health Survey was done. This was a cross-sectional study of ever-married female respondents from various regions of the Philippines who experienced a live birth two years prior to the interview. For this study, information from 3,592 respondents was deemed complete for analysis. Postpartum hemorrhage was assessed from self-reports as elicited from a face-to-face interview. Inadequate prenatal care was divided into two components: (1) inadequate utilization, as measured by the frequency of visits and the timing of prenatal care utilization; and (2) non-receipt of certain components of prenatal care, health behavior advice in particular. Multiple logistic regression revealed that inadequate prenatal care was associated with postpartum hemorrhage. Specifically, inadequate utilization of prenatal care was found to be associated with postpartum hemorrhage, but in addition to parity, socio-economic status is also an effect modified. This relationship was confounded by maternal age. Though statistical significant, the findings should be treated as exploratory and should be verified in further studies.